(untitled) (Global Journal of Human-Social Science, 2012)
Intensive English Programme IEP at Universiti Tenaga Nasional UNITEN is designed to measure candidates level of English language proficiency and to determine whether they are ready to undertake a course at tertiary level in English At UNITEN many foreign students are currently undergoing the IEP Programme at the College of Foundation and General Studies CFGS before they can pursue their studies at the respective colleges in UNITEN However majority of the students lack the prerequisite language knowledge and reading skills to cope with the IEP reading comprehension tests Many of them have problems with recognizing linguistic cues as well as locating the main ideas in discourses and paragraphs This was an experimental action research project investigating the effectiveness of a reading model The objectives of this study were 1 To investigate the EFL students reading comprehension problems specifically tunnel vision during the IEP classes 2 To evaluate the effectiveness of the Reading Model Graphic Organizer and Paragraph Frame GOPF utilized by the researcher 3 To suggest a Reading Model that can assist to boot up the IEP students attitude motivation and reading skills skimming and scanning Survey method was utilized to obtain responses from students and interview sessions were conducted to gain better insight on the students attitude and motivation Findings denote a significant improvement in the students attitude motivation and reading skills skimming and scanning at the end of the experimental research project